2017
DOI: 10.3389/fmicb.2017.00206
|View full text |Cite
|
Sign up to set email alerts
|

Common Distribution of gad Operon in Lactobacillus brevis and its GadA Contributes to Efficient GABA Synthesis toward Cytosolic Near-Neutral pH

Abstract: Many strains of lactic acid bacteria (LAB) and bifidobacteria have exhibited strain-specific capacity to produce γ-aminobutyric acid (GABA) via their glutamic acid decarboxylase (GAD) system, which is one of amino acid-dependent acid resistance (AR) systems in bacteria. However, the linkage between bacterial AR and GABA production capacity has not been well established. Meanwhile, limited evidence has been provided to the global diversity of GABA-producing LAB and bifidobacteria, and their mechanisms of effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 55 publications
(94 reference statements)
1
75
0
Order By: Relevance
“…The biosynthesis of GABA by microorganisms is performed by the glutamic acid decarboxylase (GAD, EC 4.1.1.15) system, which is composed of the GAD enzyme (encoded by gadA or gadB) and glutamate/GABA antiporter GadC [29][30][31][32][33]. The biosynthetic pathway of GABA by microbes is shown in Figure 1.…”
Section: Biosynthetic Pathway Of Gaba In Labmentioning
confidence: 99%
“…The biosynthesis of GABA by microorganisms is performed by the glutamic acid decarboxylase (GAD, EC 4.1.1.15) system, which is composed of the GAD enzyme (encoded by gadA or gadB) and glutamate/GABA antiporter GadC [29][30][31][32][33]. The biosynthetic pathway of GABA by microbes is shown in Figure 1.…”
Section: Biosynthetic Pathway Of Gaba In Labmentioning
confidence: 99%
“…These results were closely related to the findings by Hiraga et al [ 32 ] who suggested that the gad gene of Lactobacillus brevis IFO 12005 was 1,440 bp. Moreover, Wu et al [ 19 ] reported that biochemical analysis and genetic screening have confirmed the common existence of gad system in Lactobacillus brevis suggesting its species-specific characteristic of GABA production.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained results were consistent with those of Zhang [ 46 ], who showed the performance of antiacids of isolated strains. In addition, Wu et al [ 19 ] reported that pancreatic fluid had no significant effect on survival of LAB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABA is mainly converted from l -glutamate (Glu) by lactic acid bacteria (LAB) and Escherichia coli strains with high Glu decarboxylase (GAD) activity (Li and Cao 2010 ; Shi et al 2016 ). Although production of GABA by LAB, such as Lactobacillus brevis (Shi et al 2017b ; Wu et al 2017 ), is recognized as safe, the cost of production is high; whereas production of GABA by E. coli is high yield (Huang et al 2016 ; Zhao et al 2016a ) but is not acceptable for food usage. Furthermore, Glu must be added as the precursor during GABA production by LAB and E. coli , making such bioconversion not cost-effective.…”
Section: Introductionmentioning
confidence: 99%